Importancia de los programas de prevención y protección contra caídas para el control de accidentes en trabajadores que realizan actividades de altura en Colombia - Rodríguez Sierra, Emmanuel (Ciencias Administrativas, Económicas y Contables, 2017)
This article aims to show the importance of prevention programs and fall protection to control accidents in workers performing activities in Colombia height, the company and especially the department humans resources provide all the necessary tools to control accidents. Likewise, the Colombian government provides the regulatory program of protection and prevention against falls from heights through Resolution 1409 of 2012, in order to control and reduce accidents caused by work activities at height